Diagnosis and treatment of primary hepatic lymphoma - Yang, Huayu; Yang, Ziyi; Sang, Xinting; Mao, Yilei; Lu, Xin; Zhong, Shouxian; Xu, Haifeng (Translational Cancer Research; Vol 7, No 3 (June 27, 2018): Translational Cancer Research, 2018)
Background: Primary hepatic lymphoma (PHL) is one of the rare diseases in liver and there has been few researches demonstrate its clinical features in recent years. This article selects nine PHL cases and the clinical presentation, pathologic features, diagnosis and outcome of them are fully described. Methods: The clinical records of patients with liver lymphoma from Mar 1st, 2000 to Nov 30th, 2016 in the single center-Peking Union Medical College Hospital (PUMCH)-were reviewed. Nine patients were found to have PHL, which were all pathologically diagnosed. The laboratory, imaging, histologic immunohistochemical results, treatment schema and outcome of them were collected and summarized in this article. Results: In our cases, the top three frequently presenting features included B symptoms, abdominal pain and hepatosplenomegaly. The imaging features of patients revealed solitary, multiple and diffuse lesions, which were hypoechoic in ultrasounds and hypoattenuating in computed tomography (CT). The treatment regimens included surgery, chemotherapy, autologous hepatocyte transplantation and supportive therapy. The median survival time was 21.3 months. Conclusions: Patients who had primary liver lymphoma tended to present some non-specific clinical and laboratory features, increasing the difficulty of diagnosis. As PHL was often misdiagnosed as other hepatic diseases and had a poor prognosis, it should be given enough attention and specific treatment strategy was recommended.